Impact of adiposity on muscle function and clinical events among elders with dynapenia, presarcopenia and sarcopenia: a community-based cross-sectional study - Kao, Tung-Wei; Peng, Tao-Chun; Chen, Wei-Liang; Han, Der-Sheng; Chen, Chi-Ling; Yang, Wei-Shiung (Aging (Albany, NY.), 2021)
Low muscle function determined unfavorable clinical outcome than low muscle mass; nevertheless, comparison of detrimental parameters among dynapenia, presarcopenia and sarcopenia was sparse. We hypothesized that adiposity is implicated in low muscle function related adverse events. We recruited community elders to measure handgrip strength and walking speed. Using bioelectronics impedance analyzer to examine body compositions. The faller is indicated of having a fall event in the past one year. Associations of different obesity parameters, metabolic syndrome (MetS) and fall among the groups were analyzed. Among 765 participants, the dynapenia group had higher metabolic profiles, body fat percentage (BFP), waist circumference, and fat to muscle ratio (FMR) than the other groups, whereas the presarcopenia subjects had the lowest obesity parameters. The fallers tended to have poorer muscle function than non-fallers (p<0.001). The dynapenia individuals had the highest risk for MetS (odds ratio [OR]= 5.79; 95% confidence interval [CI]= 2.45-13.73), and the highest fall risk (OR= 3.11; 95% CI=1.41-6.87). Among obesity parameters, FMR had better diagnostic performance to estimate low muscle function, followed by BFP. Dynapenia individual had higher risk of obese-related adverse events. Increased adiposity irrespective of muscle mass is relevant to reduced muscle function among elders.